Pengaruh Work Life Balance dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Demandailing Cafe and Eatery) - Andrianto, Aan; Arfah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
This study aims to examine the influence of work life balance and work environment on employee performance in the study of Demandailing Cafe and Eatery employees. This research method is quantitative research and the sampling technique in this research uses a questionnaire. The number of samples used was 67, using the Random Sampling method. Data test analysis uses multiple linear regression and hypothesis testing includes the t test and F test. The t test shows that the t count is 2.808 ≥ t table 1.999 Sig value. 0.007 ≤ 0.05 shows that Work Life Balance has a significant effect on employee performance and t count is 3.441 ≥ t table 1.999 and the Sig value. 0.001 ≤ 0.05 then the Work Environment variable has a partial and significant influence on Employee Performance. The calculated f result is 15.344 ≥ f table 3.14 and the sig value. 0.000b ≤ 0.05, then the results of this study indicate that Work Life Balance and Work Environment significantly influence employee performance.